Delamination properties of laminated glass windows subject to blast loading. (July 2017) - Del Linz, Paolo; Hooper, Paul A.; Arora, Hari; Wang, Yi; Smith, David; Blackman, Bamber R.K.; Dear, John P.
Highlights: PVB delamination is proposed as an energy absorption mechanism for laminated glass. Pre-cracked laminated glass tensile tests were performed. Results showed the presence of a distinct force plateau. Delamination energies were calculated using FEA for four deformation speeds. Abstract: Delamination processes absorb significant amounts of energy in laminated glass windows when they are subjected to blast loads. Blast tests were performed previously and their results had been used to calculate the loads imposed on the support systems. In this research, the delamination process at realistic deformation rates was studied to understand the reaction force response obtained. Laboratory tensile tests were performed on pre-cracked laminated glass specimens to investigate their delamination behaviour. The experiments confirmed the presence of a plateau in the force-deflection graphs, suggesting that the delamination process absorbed significant energy. The experimental results were then employed to calibrate FEA models of the delamination process with the aim of estimating the delamination energy of the polyvinyl butyral (PVB) membrane and glass layers and its relationship with deformation speed. The delamination energies obtained through this research, if used with the appropriate PVB material model, are a valuable new tool new tool in the modelling and design of laminated glass façade structures.